2003
DOI: 10.1007/s00122-003-1291-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of alternative silvicultural systems in coastal montane forests: western hemlock and amabilis fir

Abstract: Genetic diversity and mating system were quantified for shelterwood, patch cut and green tree-retention silvicultural systems, and compared to adjacent old-growth. This is a component of a larger study conducted in montane old-growth forests of coastal British Columbia to evaluate the feasibility and ecological consequences of alternative silvicultural systems. The experiment includes replicated treatments representing a range of overstory removal adjacent to old-growth and clearcut areas. Based on 22 electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 44 publications
1
22
1
1
Order By: Relevance
“…Sarg. (El-Kassaby et al, 2003) and for Pinus caribaea Morelet (Zheng and Ennos, 1997; but see contrary results in Neale and Adams, 1985;El-Kassaby and Jaquish, 1996). We suggest that the apparent increase of consanguineous matings after cutting found in the present study could be due solely to sampling error (for they are far from significant).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Sarg. (El-Kassaby et al, 2003) and for Pinus caribaea Morelet (Zheng and Ennos, 1997; but see contrary results in Neale and Adams, 1985;El-Kassaby and Jaquish, 1996). We suggest that the apparent increase of consanguineous matings after cutting found in the present study could be due solely to sampling error (for they are far from significant).…”
Section: Discussioncontrasting
confidence: 79%
“…Most studies have compared genetic diversity of adult stands with that of naturally regenerated recruits, under alternative cutting methods (Neale, 1985;Adams et al, 1998;Rajora, 1999;Thomas et al, 1999;El-Kassaby, 2000;Glaubitz et al, 2000;Perry and Bousquet, 2001;El-Kassaby et al, 2003). Some studies suggest a small loss of low-frequency alleles among residual trees and natural regeneration, subsequent to shelterwood harvesting (Adams et al, 1998), but most studies have failed to find any significant effects of silvicultural practices on genetic diversity measures of regenerated stands.…”
Section: Introductionmentioning
confidence: 95%
“…Genetic diversity was decreased in Picea glauca (Rajora, 1999) after artificial regeneration and in Swietenia macrophylla after logging (Gilles et al, 1999). In Tsuga heterophylla the genetic diversity was lower in patch cut and shelterwood stands than in natural stands (El-Kassaby et al, 2003). On the other hand, no significant differences in genetic diversity parameters were found between path cut, shelterwood and natural stands in Abies amabilis (ElKassaby et al, 2003), In Douglas-fir no effect was observed after shelterwood or thinning compared to no-management (Neal, 1985;El-Kassaby and Benowicz, 2000).…”
Section: Introductionmentioning
confidence: 90%
“…The genetic consequences of forest management receive more attention nowadays, but are still restricted to conifers (Buchert et al, 1997;Rajora, 1999;El-Kassaby et al, 2003;Macdonald et al, 2001;Adams et al, 1998), some tropical species (Gilles et al, 1999;Lee et al, 2002) and the genus Eucalyptus (Glaubitz et al, 2003a,b). However, conflicting results were presented for different species.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the diversity of tree species and tree size is a factor of stand establishment that should be considered during regeneration (WANG and CHEN, 2010). In addition, an increased mixture of plantation and natural regeneration areas may serve to increase the genetic diversity of the forests (EL-KASSABY et al, 2003). However, unpredictable factors such as changes in climatic conditions and/or pests need to be assessed when such clusters occur (PARKS and BEMIER, 2010).…”
Section: Discussionmentioning
confidence: 99%